(3ejRGf GdYbhds - (3GdThjgj, GdMejOj, GdfLaj, GdMScj, GdMdj, CHh LYaQ, eMeO Hf LYaQ Hf jhfS Hf QGVj, cGf MjG (B1229(3g`s ((3YHO Gddg Hf eMeO MSf GdTQhbjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj YdG HQHhHjJg hbgQ GdLHGHQI HYRJg (B...s
(3BNQgG (B:s
(3Efj fXQJ aj cJH eYJHQI hQGLYJ RHQG eWhdI(B... (3Je GdLRA GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B197s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdadSaI hGdefWbs